The Concept of Mysticism in Islam and Christianity - Sahri Sahri (Graduate Program of Pontianak Institute of Islamic Studies, 2021)
Judging from its origin, there is an opinion that Sufism originates from Islam. Some say that Sufism is influenced by the practices of other religions, such as the practices of Christian priesthood and of other religions. This article aims to examine the comparison between the concepts of zuhud (asceticism / detachment) and wahdat al-wujud (the unity of existence) in Islam and the concepts of asceticism and hypostatic union in Christianity. In Christianity there is a clerical structure, but Islam does not recognize or implement it. Islamic Sufis did not transform Sufism from Christianity or other religions because Sufism is related to human instincts. Additionally, the human soul is the same despite different societies and nations. The similarities of the practice of asceticism cannot be sufficiently used as the reason that it stems from Christian asceticism. There are in fact similarities between the concept of wahdat al-wujud and hypostatic union in Christianity. The differences between the two lies in the esoteric and exoteric dimensions. However, according to al-Junaid and al-Ghazali, mahabbat and ma'rifat are the limitations of the maqam of Sufism, a level of maqam where man is still in a state of understanding of his own existence. So, between man and God, there is still distance. In this modern era, there is a need for a re-interpretation of Sufism in which Sufism is not only oriented to be purely transient to be in union with God, but it is a form of fulfilling our obligations as God's caliphs who should improve things for fellow humans and other living beings. In other words, Sufism not only contains a theophanic dimension of transience, but also a profane dimension in which there are of fellow human interests worldwide.